Factor I autoantibodies in patients with atypical hemolytic uremic syndrome: disease-associated or an epiphenomenon? - Kavanagh, D; Pappworth, I; Anderson, H; Hayes, C; Moore, I; Hunze, E; Bennaceur, K; Roversi, P; Lea, S; Strain, L; Ward, R; Plant, N; et al. (2012)
BACKGROUND AND OBJECTIVES: Atypical hemolytic uremic syndrome is a disease associated with mutations in the genes encoding the complement regulators factors H and I. In addition, factor H autoantibodies have been reported in ∼10% of patients with atypical hemolytic uremic syndrome. This study searched for the presence of factor I autoantibodies in atypical hemolytic uremic syndrome. DESIGN, SETTING, PARTICIPANTS, and MEASUREMENTS: This study screened 175 atypical hemolytic uremic syndrome patients for factor I autoantibodies using ELISA with confirmatory Western blotting. Functional studies using purified immunoglobulin from one patient were subsequently undertaken. RESULTS: Factor I autoantibodies were detected in three patients. In one patient with a high titer of autoantibody, the titer was tracked over time and was found to have no association with disease activity. This study found evidence of an immune complex of antibody and factor I in this patient, but purified IgG, isolated from current serum samples, had only a minor effect on fluid phase and cell surface complement regulation. Genetic analysis of the three patients with factor I autoantibodies revealed that they had two copies of the genes encoding factor H-related proteins 1 and 3 and therefore, did not have a deletion commonly associated with factor H autoantibodies in atypical hemolytic uremic syndrome. Two patients, however, had functionally significant mutations in complement factor H. CONCLUSIONS: These findings reinforce the concept of multiple concurrent risk factors being associated with atypical hemolytic uremic syndrome but question whether autoantibodies per se predispose to atypical hemolytic uremic syndrome.